Hypoosmotic swelling test in epididymal ram (Ovis aries) spermatozoa - Vásquez J. (2013)
This research was supported in part by the Peruvian National Council of Sciences, Technology and Innovation (CONCYTEC) through the Grant PROCYT315-2009 .